2013
DOI: 10.1097/fjc.0b013e31828f8d45
|View full text |Cite
|
Sign up to set email alerts
|

The Ginsenoside Rg1 Prevents Transverse Aortic Constriction–Induced Left Ventricular Hypertrophy and Cardiac Dysfunction by Inhibiting Fibrosis and Enhancing Angiogenesis

Abstract: Ginsenoside Rg1 exhibited protective effect against TAC-induced left ventricular hypertrophy and cardiac dysfunction, which is potentially associated with phospho-Akt activation and p38 MAPK inhibition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
40
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(50 citation statements)
references
References 31 publications
6
40
0
Order By: Relevance
“…Ginsenosides exhibit different activities on HIF‐1α and its downstream genes under distinct pathological conditions. For example, HIF‐1α levels were upregulated by Rg1 in neonatal rat brains following hypoxia/ischemia injury and rat heart tissue, as well as by Rb1 in hypoxia neonatal cardiomyocytes . However, HIF‐1α expression is downregulated by Rg3 in several cancer cell lines, including human ovarian cancer cells (e.g., SKOV3 and 3AO, bone marrow stromal cells isolated from acute leukemia patients, and human esophageal carcinoma cells [i.e., EC109, TE1, and KYSE170]) and two tumor mice models, including Lewis lung cancer cell xenografted mice and SKOV3 cells xenografted into nude mice .…”
Section: Cellular Stress Response Mechanisms Regulated By Ginsenosidesmentioning
confidence: 99%
See 1 more Smart Citation
“…Ginsenosides exhibit different activities on HIF‐1α and its downstream genes under distinct pathological conditions. For example, HIF‐1α levels were upregulated by Rg1 in neonatal rat brains following hypoxia/ischemia injury and rat heart tissue, as well as by Rb1 in hypoxia neonatal cardiomyocytes . However, HIF‐1α expression is downregulated by Rg3 in several cancer cell lines, including human ovarian cancer cells (e.g., SKOV3 and 3AO, bone marrow stromal cells isolated from acute leukemia patients, and human esophageal carcinoma cells [i.e., EC109, TE1, and KYSE170]) and two tumor mice models, including Lewis lung cancer cell xenografted mice and SKOV3 cells xenografted into nude mice .…”
Section: Cellular Stress Response Mechanisms Regulated By Ginsenosidesmentioning
confidence: 99%
“…For instance, Rg1 plays a neuroprotective role in brain repair after hypoxia/ischemia brain injury through increasing neural survival and facilitating angiogenesis . Rg1 also alleviated the pressure‐overloaded cardiac dysfunction in a rat model of left ventricular hypertrophy induced by transverse aortic constriction, which is at least partly related to enhanced angiogenesis . Rb1 inhibited apoptosis of hypoxia‐insulted neonatal rat cardiomyocytes by upregulating the HIF‐1α‐dependent apelin–APJ system …”
Section: Cellular Stress Response Mechanisms Regulated By Ginsenosidesmentioning
confidence: 99%
“…Ginsenoside Rg1 is one of the primary active compounds in P. ginseng and has been shown to inhibit inflammation and oxidative stress [9, 10]. Zhang et al demonstrated that ginsenoside Rg1 could alleviate myocardial fibrosis induced by transverse aortic constriction [11]. Xie et al found that ginsenoside Rg1 significantly attenuated the development of renal interstitial fibrosis in a rat unilateral ureteral obstruction model, perhaps through a reduction of transforming growth factor β 1 (TGF- β 1) [12, 13].…”
Section: Introductionmentioning
confidence: 99%
“…26 Moreover, the ginsenosides Rb1 and Rg1, and tetrahydropalmatine enhanced angiogenesis by increasing the expression of hypoxia inducible factor-1 and vascular endothelial growth factor in vivo. [26][27][28] Collectively, bioactive components in Shen-yuan facilitate the recovery of haemodynamic function after MI.…”
Section: Discussionmentioning
confidence: 99%